A New Bone Marrow Transplantation Method for the Prevention of Graft- Versus-Host Disease - Ikehara, Susumu (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
A new bone marrow transplantation (BMT) method,
Keywords: Bone marrow transplantation